(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It is known that when an artist creates a work of art, he strives to make it unique and remain in people’s memory for a long time, he uses all his talent. In this way, he tries to make full use of his native language. The creator’s "invention" in a certain sense is manifested in the form of occasional units. We can find many such units in the work of the poet Erkin Vahidov. The poet used occasional units very appropriately. This ensures that the text of the poem does not contain excessive repetitions and repetitions